E-community system towards first class mentality development: an infrastructure requirements analysis - Abdullah, Rusli; Abu Hassan, Musa; Omar, Siti Zobidah; Ismail, Narimah; Bolong, Jusang (Canadian Center of Science and Education, 2010)
E-Community portal can be classifed as an extension of normal type of knowledge management system (KMS) development towards first class mentality. It servers varities of expects in term of capabilities and services especially for the benefits of community. Most of the community today are looking on this matter as a very important issue and try to search the best way to manage or organize this community system for sustain a high rate of continuous improvement. While e-community system (ECS) or portal is a system that related to the process of knowledge capture, re-use, searching and representation to the user in a variety of form. The role of system could be determined by looking on the issues on how knowledge can be applied at the right time in the faster ways that based on the simplest command or agent given to the system in order to get the relevant knowledge from the portal. Besides that, system also could be looked on how the best element of infrastructure requirement could be used for, in the benefits of users in order to stored and captured as well as presenting the knowledge portal. The paper presents the analysis of the ECS infrastructure requirement, and its system implementation in a community of practise (CoP) especially towards first class mentality development as well as discussing a variety issues that related to its involvement, so that it will help CoPs to increase their productivity and quality as well as to gain return on investment (ROI).